Epidemiological Study of Mycosis in Bronchopulmonary Infections and Antifungal Susceptibility Testing in Diyala, Iraq - Mohammed, Najwan Abbas (AlQalam Journal of Medical and Applied Sciences, 2025)
Fungal lung diseases, encompassing a wide range of pathogens and their associated clinical symptoms, are a major global health challenge. The nature and severity of the disease depend on both host immunity and the infecting fungal strain. This study aimed to isolate and Identification of fungi causing respiratory infection and allergic bronchopulmonary mycosis and study their response to locally available antifungals. Fifty-three samples (21 females and 32 males) were collected from patients with respiratory infections and allergic bronchopneumonia in Diyala\ Iraq. The samples were examined by culture media and microscopically to determine the fungal species. Antifungals were tested by the disc diffusion method. ABPM was detected in 69.8 % of the study group with highly significant differences (P≤0.01). Males were more affected than females, with a percentage of 78.1% with significant differences (P≤0.05). Respiratory Mycosis (RM) was more prevalent in the age group (40- 49). There were highly significant differences in fungal infections among age groups. Candida species were the most isolated species that caused RM, followed by Aspergillus spp. Penicillium spp. were detected in 18.9%, Cryptococcus and Blastomyces were detected in four (10.8%) isolates each, Cladosporium, Mucor, and Alternaria were detected in one (2.7%) isolate each. Some samples contain more than one species. 24.3% of fungal infections were detected in patients in Diyala Central Prison, Baqubah city, showing 18.9% of fungal infections. Candida and Cryptococcus were most affected by Clotrimazole and Fluconazole. Amphotericin and Clotrimazole have good effects on Penicillium. Alternaria was sensitive to Clotrimazole, Fluconazole, and Amphotericin B.